Analyzing Unimar’s Positioning Strategy for Strengthening Brand Image and Increasing Student Enrollment - Atmaja, Sena; Dadang, Dadang; Ayudya, Dila (Universitas Muhammadiyah Tangerang, 2025)
This study analyzes the positioning strategy of Universitas Muhammadiyah A.R. Fachruddin (Unimar) in building its brand image to increase new student enrollment. Using a mixed methods approach, combining interviews with institutional stakeholders, surveys of 150 respondents, and SWOT, IFAS–EFAS, and QSPM analyses, research found that Unimar’s Islamic identity is its primary strength (recognized by 72% of respondents) but remains largely symbolic, with weak differentiation (40%), limited brand awareness (45%), and underdeveloped academic reputation. IFAS (2.60) and EFAS (2.90) place Unimar in Cell II (Grow and Build) of the IE Matrix, suggesting the need for aggressive growth strategies. QSPM results prioritize strengthening Islamic identity through integrated digital marketing, followed by the development of Islamic-modern flagship programs and enhancement of academic reputation. The study contributes theoretically to higher education marketing literature and provides practical recommendations for Unimar to enhance competitiveness and ensure sustainable student enrollment growth.